Latent structure and measurement invariance by gender of the Embodied Image Scale - Volarov, Marija; Janičić, Bojan; Popov, Stanislava; Barzut, Vesna (Primenjena psihologija, 2024)
Body image is a multidimensional construct that includes both aesthetic (how our body looks) and functional components (what our body can do physically). Our study aimed to investigate latent structure and measurement invariance (MI) by gender of the Serbian translation of Embodied Image Scale using a large sample of adults from the general population (N = 1035; M = 26.33, SD = 9.94; 66.7% females). The Embodied Image Scale (EIS) incorporates aesthetic and functional body image. According to the results of the confirmatory factor analysis, the following five factors described the latent structure of the EIS the best: functional investment (FI), functional values (FV), functional satisfaction (FS), aesthetic satisfaction (AS), and aesthetic values and investment (AVI). The results of the MI suggested that the EIS achieved the strict (residual) level of invariance. In addition, the convergent validity of the EIS was tested by correlating the EIS scores with positive and negative mental health indicators. The results suggested that FV, FI, FS, and AS had a positive correlation with positive affect and unconditional self-acceptance (USA), FS and AS correlated negatively with negative affect (NA), symptoms of depression (D), and conditional self-acceptance (CSA), while the AVI had a positive correlation with NA, CSA, D, and negative correlation with USA. Finally, we compared physically inactive participants, recreationists, and active athletes on the EIS scores. The results revealed that all groups differed in FV, FS, and AS in a way that scores on these subscales increased with increased physical activity.